Crisis, agency and negotiating gender identity: an ethnographic study of female participants in the Zār ritual in the Hormozgān Province of Iran - Abbasi, Maryam (Shaman, 2019)
In southern Iran, the zār ritual is a community-based activity which is used to treat people who are believed to be possessed by spirits. The most important spirit, called zār, gives the possessed person a divine power in the eyes of others, in which she/he is allowed to ignore some social norms and enjoy societal respect without any punishment. From 2010 to 2016 I interviewed over fifty participants and non-participants in the zār ritual and reviewed the literature in order to evaluate different aspects of the ritual. My fieldwork indicates that the zār participants tend to be the most vulnerable and powerless members of society, who through their participation are able to avoid some of their gender-based predicaments and particular crises. The main research questions I sought to answer are: What are the predicaments and crises which lead women to turn to the zār ritual for help? And how does participation in the zār ritual facilitate their recovery? How do the women see this process?